Mechanical design and wheel–leg–body cooperation control of a step‐climbing robot. Issue 7 (6th June 2022) - Liu, Chong; Zhang, Xinde; Wu, Renqiong; Wang, Shixiong; Wang, Ruchao; Lu, Zhiguo; Xiao, Yinhe; Li, Songhao; Wu, Zhuohang
Abstract: This paper proposes the mechanical design and wheel–leg–body cooperation control of a robot capable of climbing stairs for the RoboMaster competition. The robot is comprised of a robot body and four legs with wheels on each end. The front and hind legs composed of the linkages and sliders complete the climbing stairs motion under the coordination of the motors and the cylinders. The dynamic stair‐climbing motion is realized by control the wheel speed and leg motion corresponding to the body motion of the robot relative to the stair environment. Compared with the common split stair climbing designed, the robot can dynamically climb the stairs without losing the forward speed, which makes climbing stairs more smoothly while retaining the ability to move on the flat. Experimental results demonstrate that the robot can climb stairs with a riser height up to 20 cm and a tread depth more than 80 cm. And the process of climbing each stair is reduced to 1–2 s.